Nepotisme yang Mengakar: Intitusi Informal dan Erosi Integritas Administratif - Yulianty Mozin; Alfiyah Agussalim; Putri Salsabila Naleko; Wulandari Mantali; Siti Nafisyah Tulong; Jaden Junior Alimun; Rivaldi Saputra Ibrahim (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
This study aims to examine how nepotism can manifest through the role of informal institutions and its influence on administrative integrity within the bureaucracy. The method used is literature analysis by examining various related scientific references, such as books, journal articles, and research, which are then analyzed descriptively and analytically through identification, classification, and data integration. The research findings indicate that nepotism does not only arise from weaknesses in the official system, but is also strongly influenced by the existence of informal institutions such as personal networks, social norms, and organizational culture. This practice tends to persist within a system because it gains social recognition, making it difficult to overcome solely with regulations. The consequences include a decline in employee professionalism, weak accountability, and erosion of administrative integrity, which impacts on reduced public trust in government institutions. The implications of this study indicate that a comprehensive approach is crucial in bureaucratic reform, through strengthening the official system and changing organizational cultural values ​​to produce transparent, accountable, and dignified government management.